2017
DOI: 10.4055/cios.2017.9.1.10
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of the Causes and Predictors of 30-Day Mortality Following Hip Fracture Surgery

Abstract: BackgroundA fracture neck of femur is the leading cause of injury-related mortality in the elderly population. The 30-day mortality figure is a well utilised marker of clinical outcome following a fracture neck of femur. Current studies fail to analyse all patient demographic, biochemical and comorbid parameters associated with increased 30-day mortality. We aimed to assess medical risk factors for mortality, which are easily identifiable on admission for patients presenting with a fractured neck of femur.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 28 publications
4
74
1
1
Order By: Relevance
“…In a large retrospective study of 38 020 hip fracture patients, an overall 30‐day mortality of 10% was found . In a similar study of 1356 patients, the 30‐day mortality was 8.7% following hip fracture surgery . Our data on time from admission to surgery are close to the Danish national quality index target of having surgery within 24 hours of admission with a hip fracture.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In a large retrospective study of 38 020 hip fracture patients, an overall 30‐day mortality of 10% was found . In a similar study of 1356 patients, the 30‐day mortality was 8.7% following hip fracture surgery . Our data on time from admission to surgery are close to the Danish national quality index target of having surgery within 24 hours of admission with a hip fracture.…”
Section: Discussionsupporting
confidence: 75%
“…Hip fracture occurs in approximately 100 of 100 000 people each year . Most hip fractures occur among the elderly and the perioperative mortality is substantial; 30‐day mortality is estimated to be between 5% and 13% . The underlying causes have been assessed in several studies and non‐modifiable factors such as age and pre‐existing comorbidities contribute to early death among hip fracture patients .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, intertrochanteric fracture induces more bleeding and requires a longer operation time, more complicated surgical methods and requires avoiding full weight-bearing exercise after the operation. As a result, patients with intertrochanteric fracture showed a higher mortality rate than patients with femoral neck fracture [13][14][15]. However, there were also reports that there was no difference in mortality rates between the two fracture types [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…(5,8) About 9% to 11% of hip fracture patients have been reported to develop hospital-acquired pneumonia and 4% to 17.9% to develop urinary tract infection, (8)(9)(10)(11) within a varying follow-up time window spanning from during admission to 6 months of follow-up. Pneumonia is a leading cause of death among hip fracture patients, (12,13) and is associated with an excess mortality risk among hip fracture patients. (8,14,15) It has been suggested that the decrease in mortality among hip fracture patients over the last 20 years could be explained by improvement in both perioperative and postoperative patient care.…”
Section: Introductionmentioning
confidence: 99%